Sub-millimeter fiberscopic robot with integrated maneuvering, imaging, and biomedical operation abilities - Tieshan Zhang; Gen Li; Hao Ren; Liu Yang; Xiong Yang; Rong Tan; Yifeng Tang; Dong Guo; Haoxiang Zhao; Wanfeng Shang; Yajing Shen (Nature Communications)
Abstract Small-scale continuum robots hold promise for interventional diagnosis and treatment, yet existing models struggle to achieve small size, precise steering, and visualized functional treatment simultaneously, termed an “impossible trinity”. This study introduces an optical fiber-based continuum robot integrated imaging, high-precision motion, and multifunctional operation abilities at submillimeter-scale. With a slim profile of 0.95 mm achieved by microscale 3D printing and magnetic spray, this continuum robot delivers competitive imaging performance and extends obstacle detection distance up to ~9.4 mm, a tenfold improvement from the theoretical limits. Besides, the robot showcases remarkable motion precision (less than 30 μm) and substantially widens the imaging region by ~25 times the inherent view. Through ex vivo trials, we validate the robot’s practicality in navigating constrained channels, such as the lung end bronchus, and executing multifunctional operations including sampling, drug delivery, and laser ablation. The proposed submillimeter continuum robot marks a significant advancement in developing biomedical robots, unlocking numerous potential applications in biomedical engineering.